Enhancing The Product Value of Bitter Melon Chips Through Branding at Home Industry Melati - Rizki, Via Lailatur; Masyhuri, Masyhuri; Muttaqien, Fauzan; Permadi, I Komang Oka (Empowerment Society, 2025)
Home industries play a vital role in the local economy. However, some small-scale businesses struggle to compete due to limited product value and the lack of branding. One example is the Melati Home Industry in Jatiroto Village, Lumajang Regency, which produces bitter melon chips but lacks strong branding. This community service activity aims to strengthen product value through branding, including logo creation, packaging design, and attention to product quality. The method used is participatory training and mentoring, including branding strategies and the use of production aids such as spinners to improve product quality. The results of this activity show a improvement to the partner’s understanding of the importance of branding and its application to their businesses. Partners successfully created new product logos and labels, utilized standing pouch and jar packaging, and utilized spinners and impulse sealers to improve product neatness and hygiene.